Beliefs, attitudes, and intentions for allowing elephants in group ranches around amboseli national park, Kenya. (15th June 2013) - Browne‐Nuñez, Christine; Jacobson, Susan K.; Vaske, Jerry J.
ABSTRACT Wildlife authorities and conservationists are working to improve attitudes toward elephants (Loxodonta africana) among residents of the Greater Amboseli Ecosystem in southern Kenya; yet information on existing attitudes and their antecedents is lacking. In 2005, we conducted a survey of 569 randomly selected residents of group ranches—communally held lands around Amboseli National Park—to 1) identify intentions to allow elephants in group ranches, 2) examine attitudes toward this behavior, 3) explore underlying beliefs that influence attitudes, and 4) identify socio‐demographic predictors of residents for and against elephants in group ranches. A slight majority (53%) supported elephants in the group ranches and 47% were opposed. Residents who favored elephants in group ranches were more likely to believe that allowing elephants would increase opportunities to see elephants and attract more tourists to visit group ranches. Those opposed believed that it would cause conflict between people, increase dangerous human–elephant interactions, and increase costs to local people. Both groups believed allowing elephants in the group ranches would cause elephants to increase in number, but those in favor gave this outcome a positive evaluation, whereas those opposed felt this was a negative outcome. Women were less positive than men toward allowing elephants outside the park. Information on beliefs and evaluations of outcomes associated with allowing elephants in group ranches can assist stakeholder groups in addressing concerns of local people and developing interventions to facilitate the continued coexistence of people and elephants. © 2013 The Wildlife Society.